Local Government Policy of Oil and Natural Gas Governance: A Case Study of Indonesia - Eliza Zuraida Zen; Thereza Efriliya N (Konsultan Surya Buanan, 2024)
This study aims to determine the policies used by the Bojonegoro Government in managing oil and gas in economic resilience and the impact on the development of oil and gas mining in the socio-economic community in Mojodelik Village, Gayam District, Bojonegoro Regency. By using qualitative descriptive methods and using data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the realization of economic resilience during the period of Regent Suyoto was achieved through the issuance of Regional Regulation Number 23 of 2011. Furthermore, the negative impacts caused by oil and gas management policies are greater than the positive impacts because the entire community feels more negative impacts such as socio-economic and environmental stability are disrupted, such as reduced community income, the location of agricultural land with houses is getting further away, reduced water absorption, reduced interaction between farmers and farm laborers, and the emergence of envy between farmers affected by land acquisition. And the positive impacts are able to help facilitate travel including speeding up travel distances and shortening travel time between regions considering that roads without obstacles speed up travel time.